2019
DOI: 10.1080/13880209.2019.1701044
|View full text |Cite
|
Sign up to set email alerts
|

Methyl lucidone induces apoptosis and G2/M phase arrest via the PI3K/Akt/NF-κB pathway in ovarian cancer cells

Abstract: Context: Methyl lucidone (ML) from the dried fruit of Lindera erythrocarpa Makino (Lauraceae) exhibits cytotoxic effects in various cancer cell lines. However, its effects on ovarian cancer cells remain unknown. Objective: This study evaluates the mechanism of ML-induced apoptosis, cell cycle distribution in ovarian cells. Materials and methods: The cytotoxic effect of ML (2.5-80 mM) on OVCAR-8 and SKOV-3 cells was evaluated by MTS assay for 24 and 48 h. Apoptosis and cell cycle arrest were analysed by flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…intrinsic mitochondrial mediated apoptosis is considered to be the more critical way of the two (Stevens and Oltean 2019;Yoon et al 2020). Mitochondrial mediated apoptosis is largely regulated by the Bcl-2 protein family.…”
Section: Discussionmentioning
confidence: 99%
“…intrinsic mitochondrial mediated apoptosis is considered to be the more critical way of the two (Stevens and Oltean 2019;Yoon et al 2020). Mitochondrial mediated apoptosis is largely regulated by the Bcl-2 protein family.…”
Section: Discussionmentioning
confidence: 99%
“…ML also led to the repression of cyclin-A/B expression and stimulated cyclin-dependent kinase inhibitors p21 and p27. Importantly, ML exerted its inhibitory downstream effects by blocking the PI3K/AKT/mTOR/NFκB axis, manifested by significant downregulation of the levels of PI3K and phosphorylated AKT concomitant with nuclear translocation of NFκB and the total level of p-IkBα [54]. Another study reported that inhibition of YAP significantly suppressed the malignant behavior of OvCa cells, via regulation of the PI3K/AKT/mTOR pathway.…”
Section: Recent Advances In Targeting Pi3k/ Akt/mtor/nfκb Axismentioning
confidence: 99%
“…The phosphoinositide 3-kinase (PI3K)/Akt-dependent pathway has been related to cell proliferation and apoptosis in several cancer cell lines, but currently the available data on the relationship between the PI3K/Akt pathway and apoptosis are conflicting. Some drugs trigger apoptosis in cancer cells via stimulation of this pathway [ 43 ], while other drugs exert an inhibitory effect [ 44 ]. A recent study showed that a new derivative of curcumin, T59, activated the PI3K/Akt pathway and induced apoptosis in lung cancer cells [ 45 ], but another study found that a combination of curcumin and paris saponin 2 (PS2) induced apoptosis in lung cancer cells through inhibition of the PI3K-Akt pathway.…”
Section: Lung Cancermentioning
confidence: 99%